IMPLEMENTASI METODE FORWARD CHAINING UNTUK MENDETEKSI PENYAKIT PADA TANAMAN KELENGKENG - Sri Ngudi Wahyuni; Santosa Santosa (Jurnal Mantik Penusa)
Kelengkeng or Dimocarpuslongan plant is one of the fruit plants that is widely developed by the community. Longan plants are very healthy with nutritional content, but unfortunately, these plants are susceptible to diseases, so it is necessary to build a system to educate the public about the symptoms and diseases of Kelengkeng fruit plants. Disease detection in this study uses the Forward Chaining method which can conclude several symptoms using the if-then rule. So, the question in this research is how to implement the Forward Chaining method for the detection of diseases in longan plants based on the knowledge base supported by an expert in agriculture and plantations.